ANALISA PEMANFAATAN CAMPURAN BRIKET ARANG SEKAM PADI DENGAN CANGKANG KEMIRI SEBAGAI BAHAN BAKAR ALTERNATIF - Sallolo Suluh (Jurnal Dynamic Saint, 2021)
This research aims to determine; (1) The effect of the mixture of rice husk charcoal briquettes with hazelnut shell charcoal on boiling time, (2) The effect of the mixture of rice husk charcoal briquettes with hazelnut shell charcoal on the net power (Pout) (3) The effect of the mixture of rice husk charcoal briquettes with hazelnut shell charcoal on the loss of power in the furnace, (4) The effect of a mixture of rice husk charcoal briquettes with hazelnut shell charcoal on the resulting thermal efficiency. The research method used is an experimental method using rice husk charcoal with candlenut shell charcoal for testing on the stove. The results showed that the most superior mixture of rice husk charcoal briquettes with hazelnut shells was found in B3 briquettes (a mixture of 40% rice husk charcoal and 40% hazelnut shells) resulted in boiling time in the 55th minute, clean power 0,24 kW, loss of power 0,098 KW and thermal efficiency of 40.45%.